Breast self-examination practice and associated factors among pastoralist women in the West Guji Zone, Oromia, Ethiopia: a community-based cross-sectional study - Mohammed Aliyi; Yimar Hotessa; Abdisa Haro; Belda Negesa Beyene; Misgana Desalegn; Derese Eshetu Debela (Frontiers in Global Women's Health)
BackgroundBreast cancer is the most common cancer among women. It is the leading or second cause of female cancer-related deaths in both developed and developing countries, including Ethiopia. Breast self-examination is an effective and efficient screening method used by women for the early detection of breast cancer. There is limited data about breast self-examination practice among pastoralist women in the study area. Therefore, the aim of this study was to assess the magnitude of breast self-examination practice and associated factors among women of childbearing age in the West Guji Zone, South Ethiopia.MethodsA community-based cross-sectional study was conducted from 1 March to 30 April 2023 on 424 randomly selected women of childbearing age in the West Guji Zone. A systematic sampling technique was employed to select the study participants. Data was collected using pre-tested and structured questionnaires through face-to-face interviews, entered into EpiData version 4.6 and then exported to SPSS version 25 for cleaning and analysis. Bivariable and multivariable analyses were conducted using binary logistic regression to identify factors associated with breast self-examination practice. Statistical significance was declared at a P-value <0.05.ResultIn this study, 62 (14.6%) of the women had a good practice of breast self-examination. Maternal age (25–34 years) [adjusted odds ratio (AOR) = 1.98, 95% confidence interval (CI): 1.07–3.70], monthly income (AOR = 3.92, 95% CI: 1.34–11.49), residence (AOR = 2.28, 95% CI: 1.09–4.78), and knowledge about breast self-examination (AOR = 2.15, 95% CI: 1.14–4.05) were factors significantly associated with breast self-examination practice.ConclusionThe study's findings indicated a significantly low level of breast self-examination practice among pastoralist women. Women's education should be promoted, income generated, and the practice of breast self-examination should be advocated.